Human Evolution: the Limits of Technocentrism - M. I. Boichenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this article is to define the limits of technocentrism through the analysis of the limiting opportunities of technique and technology from certain value positions. Theoretical basis. The philosophical anthropology of Helmut Plessner (the axiological direction in anthropology and neo-institutionalism) was the research methodology. Originality. The institutional use of technology gives it the character of a social phenomenon and turns it into technology. The ability of individuals, which is aimed at achieving a certain goal with the help of certain sustainable techniques, is not yet technology in itself but is only a certain author’s technique. Such subjectively acquired technique can be turned into socially used technology, otherwise, it will be lost. Technology is a technique that has gained recognition and has been mastered by those who did not invent it but used the algorithm proposed by the inventor, a detailed and functionally sound explanation, a method of constructing this technique. But the main thing is that technology is a technique that has received an acceptable justification for society. Conclusions. Technology is not only a means of achieving the goal, it is a way for a human being to transform the world. As such, technology is a component of human himself/herself and changes human – more precisely, a human being changed himself/herself with the help of technologies that he/she creates. However, this creates certain limits of such transformations: technology cannot replace humans in their ability to self-reproduce. Technology is always an element of social communication: the success of communication is interdependent on the success of the technology. Social modernization includes new technologies, but a more important component of social modernization is the new values for which these new technologies are created. Human evolution generates the technocratism at a certain stage. But to the extent that technocracy begins to contradict the values of humans and society, it loses its source of development – human creativity.